Effect of foliar-applied iron and zinc on growth rate and essential oil in sweet basil (Ocimum basilicum L.) under saline conditions - Elhindi, Khalid M; Al-Suhaibani, Nasser A.; El-Din, Ahmed F. Sharaf; Yakout, Sobhy M; Al-Amri, Salem M. (Progress in Nutrition, 2016)
Summary. Foliar application of some micronutrients (Fe and/or Zn) were conducted to determine whether exogenous could mitigate the adverse influences of salt stress on growth rate and essential oil content of sweet basil (Ocimum basilicum L.) plants. Sweet basil were grown under normal and various saline stress conditions, with 0.4% (ECiw 6.1 dS/m) and 0.8% (ECiw 10.8 dS/m) of sea salt irrigation. Salinity was recorded to cause a significant decrease at all the vegetative and reproductive growth characters. However, essential oil percentage, proline as well as reducing and non-reducing sugars content were increased under saline conditions. Applications of Fe through FeSO4 and Zn through ZnSO4 and their mixture by foliar were establish to increase all the growth characters and biochemical activities of sweet basil plant regardless to their growth rate under non-saline or saline stress. The growth rate and yield component by reason of the mixture of foliar spray was greater than spray of single nutrient. Regarding essential oil constituents, linalool and eugenol were the main components. Salinity treatments at 0.4% and 0.8% levels enhanced the content of linalool and, however, there was a reduction in eugenol content. Addition of micronutrients by foliar spray reduced linalool in normal conditions; on the contrary, there was an increase in linalool content by using salinity treatment. In conclusion, our results support the hypothesis that foliar application of Fe and Zn could mitigate the seawater stress of sweet basil plants.